Optimizing Thematic Pictures To Enrich Young Learners’ Vocabulary Mastery - Iman, Jaya Nur; Angraini, Nike (STMIK Royal, 2024)
Majority of Indonesian EFL young learners struggle with mastering English vocabulary. This community service activity was about to see whether or not incorporating thematic pictures could enrich young learners’ English vocabulary. It used quantitative approach with descriptive analysis. Conveniently, one class was taken as the sample of this current activity which consisted of fourteen participants coming from different grades of elementary school. A Dictation test was administered as pretest and posttest before and after intervention to portray the young learners’ achievement level. The result showed that using thematic pictures was significantly impactful in enriching young learners’ English vocabulary mastery (.00 < .05). Ultimately, some pedagogical implication were also addressed accordingly in this present activity to young learners, future facilitators as well as researchers. Keywords: thematic pictures; vocabulary mastery; young learners. Abstrak: Mayoritas pembelajar muda di Indonesia memiliki masalah dengan penguasaan kosakata Bahasa Inggris. Kegiatan Pengabdian masyarakat ini bertujuan untuk melihat apakah penggunaan gambar tematik dapat memperkaya kosa kata bahasa Inggris pelajar muda atau tidak. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis deskriptif. Mudahnya, satu kelas diambil sebagai sampel kegiatan kali ini yang terdiri dari empat belas peserta yang berasal dari berbagai tingkatan sekolah dasar. Tes Dikte diberikan sebagai pretest dan posttest sebelum dan sesudah intervensi untuk menggambarkan tingkat prestasi pelajar muda. Hasilnya menunjukkan bahwa penggunaan gambar tematik memberikan dampak yang signifikan dalam memperkaya penguasaan kosakata bahasa Inggris pelajar muda. Pada akhirnya, beberapa implikasi pedagogis juga dibahas dalam kegiatan ini kepada pelajar muda, fasilitator masa depan, serta peneliti. Kata kunci: gambar tematik; pembelajar muda; penguasaan kosakata